Evaluación de la eficacia de dos enraizantes naturales a base de lenteja (Lens culinaris) y sábila (Aloe vera) en álamo plateado y aliso en el vivero de Las Acacias del barrio San Sebastián de Salcedo durante el periodo actual. - Morales Coque, Adriana Leonela (2021)
This research had the objective of elaborating two types of natural rooting agents based on lentil and aloe by means of applications of quantities of 25ml, 50ml of lentil rooting agent and a natural control in alder seeds and silver poplar cuttings; and 25ml, 50ml of aloe rooting agent and two controls without treatment in alder seeds and silver poplar cuttings for three months after germination and corresponding sprouting, adding the treatments every 7 days. The process was carried out at Las Acacias Nursery in Salcedo canton, improving and reducing the growth time of the tree species to be treated; for the elaboration of said rooting agents, it was preferred to use only the organic materials such as aloe and lentil to clearly evaluate the benefits of each one of them, for the elaboration of the lentil-based rooting agent, two lb of product and a liter of water, which after soaking for a week we liquefy and sieve. On the other hand, for the aloe strand, taking a sheet, the entire pulp is removed, and it is triturated with ½ liter of water, the result will be a bit dense, but its absorption is improved. Then, with the amounts of the treatments of both rooting and their respective planting, it was possible to take note of growth, initially in a field notebook, each start of the week for three months to use the data in the Infostat and Excel statistical programs that helped to determine the analysis of variance and the TUKE test at 5%. The experimental design used was a DBA, in which a production method was evaluated, with two different percentages of rooting, 1 witness and 2 repetitions. It was obtained 12 treatments with 10 plants for each treatment. The germination analyses of the alder species with the 50% lentil rooting treatment reflect a percentage of 100% of germinated species, while for the treatment of silver poplar cuttings with the 50% lentil rooting treatment, obtains 100% rooting of plants; highlighting the lentil rooting as the best and most efficient; but a good effect that is also granted to the use of the natural rooting of aloe with an average effectiveness of 95% when using a 50% treatment is not ruled out, since both also turn out to be of a very economical cost, they transcend to be very striking for a decrease in the production time in “LAS ACACIAS” Nursery.